Nurses with sensory disabilities: their perceptions and characteristics. - Neal-Boylan, Leslie; Fennie, Kristopher; Baldauf-Wagner, Sara (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2011)
A survey design was used to explore the perceptions and characteristics of registered nurses (RNs) with sensory disabilities and their risk for leaving their jobs. An earlier study found that nurses with disabilities are leaving nursing and that employers do not appear to support these nurses. Work instability and the mismatch between a nurse's perceptions of his or her ability and the demands of their work increase risk for job retention problems. This study's convenience sample of U.S. RNs had hearing, vision, or communication disabilities. Participants completed a demographic form, three U.S. Census questions, and the Nurse-Work Instability Survey. Hospital nurses were three times more likely to be at risk for retention problems. Nurses with hearing disabilities were frustrated at work. Hearing difficulties increased with years spent working as a nurse. Many nurses with sensory disabilities have left nursing. Early intervention may prevent work instability and increase retention, and rehabilitation nurses are ideally positioned to lead early intervention programs.
Keywords: *Communication Disorders; *Disabled Persons; *Employment; *Nursing Staff; *Personnel Management; *Sensation Disorders; Adult; Aged; Communication Disorders; Communication Disorders/rh [Rehabilitation]; Disability; Disability Evaluation; Disabled Persons; Disabled Persons/rh [Rehabilitation]; Employment; Hearing Impaired Persons; Humans; Middle Aged; Nursing Staff; Nursing Staff, Hospital; Nursing shortage; Personnel Management; Persons With Hearing Impairments/rh [Rehabilitation]; Rehabilitation Nursing; Sensation Disorders; Sensation Disorders/rh [Rehabilitation]; United States; Visually Impaired Persons; Visually Impaired Persons/rh [Rehabilitation]; Workforces; adult; aged; article; communication disorder; dept.nur; disability; disabled person; employment; human; middle aged; nursing staff; patient; personnel management; rehabilitation nursing; sensory dysfunction